Distanced Large Group Simulations as a Learning Method for Interprofessional Collaboration - Marja Silén-Lipponen; Eija Piippo-Savolainen; Mina Azimirad; Terhi Saaranen (Nursing Reports)
Digitalization in healthcare education has shifted simulation learning methods to distanced implementations. Successful transition to distance education requires effective communication and the teacher’s good ability to use digital learning methods, as well as students’ active interaction and motivation throughout the entire educational process. This study explores participants’ experiences of online large group simulations as an approach for learning about interprofessional collaboration. A mixed method design was used in this study. Data from health and social care students and qualified professionals were collected using a questionnaire which contained statements presented on a five-point Likert scale and open-ended questions. The questionnaire was filled online by 100 students and professionals. The quantitative data were analyzed using descriptive statistical methods, and the open-ended questions were analyzed with inductive content analysis. As a result, the participants were satisfied with the large group simulation intended for learning interprofessional collaboration (mean = 4.42, SD = 0.759). The majority viewed it as a good learning method (95%) that is suitable for interprofessional collaboration learning (90%) and for promoting working together (82%). Digitally activated communication tools promoted interactive discussion and activated joint learning. However, only one activation tool was preferred instead of using two methods simultaneously. In conclusion, distanced large group simulations were evaluated to be a good method for learning interprofessional collaboration. This study was not registered.